Bladder cancer risk associated with family history of cancer. Issue 12 (5th March 2021) - Koutros, Stella; Decker, Kathy L.; Baris, Dalsu; Pardo, Larissa A.; Johnson, Alison; Hosain, G.M Monawar; Rothman, Nathaniel; Karagas, Margaret R.; Schwenn, Molly R.; Silverman, Debra T.
Abstract: Twin studies suggest a familial aggregation of bladder cancer, but elements of this increased familial risk of bladder cancer are not well understood. To characterize familial risk of bladder cancer, we examined the relationship between family history of bladder and other types of cancer among first‐degree relatives and risk of bladder cancer in 1193 bladder cancer cases and 1418 controls in a large population‐based case‐control study. Multivariate logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between family history of bladder cancer (defined as at least one first‐degree family member with bladder cancer or a cancer of any other site). We also evaluated cancer aggregation of specific sites in family members. Participants with a first‐degree relative with bladder cancer had nearly double the risk of bladder cancer (OR = 1.8, 95% CI 1.2‐2.9) as those without a family history of bladder cancer. Risk was increased for having a sibling with bladder cancer (OR = 2.6, 95% CI 1.3‐5.3) compared to no siblings with cancer. Bladder cancer risk was elevated when participants reported a first‐degree relative with a history of female genital cancer (OR = 1.5, 95% CI 1.1‐2.1), melanoma (OR = 1.9, 95% CI 1.02‐3.6), and tobacco‐associated cancer (OR = 1.3, 95% CI 1.06‐1.6). These findings add to evidence of a familial predisposition to bladder cancer. Clarification of the aggregation of bladder cancer in families and with other cancer sites will be of interest as many loci and common polymorphisms related to bladder cancer have yet to be identified in large genomic studies. Abstract : What's new? While a family history of bladder cancer significantly increases risk of developing the disease, little is known about how this risk is modified by age, gender, family characteristics, and other factors. In this study of familial bladder cancer risk, risk was found to be nearly doubled for individuals with a first‐degree relative with bladder cancer. Risk was also elevated for individuals who had a first‐degree relative affected by certain other cancers, including female genital cancers, melanoma, and cancers at tobacco‐associated sites. These findings provide clues for further investigation to help uncover the genetic basis of bladder cancer.